Durability and reutilization capabilities of a Ni-Ru catalyst for the hydrolysis of sodium borohydride in batch reactors - A. M. F. R. Pinto (2011)
The study of catalyst durability and reutilization on catalyzed hydrolysis of sodium borohydride is essential from an application point of view. Few works on this topic are available in the literature. In the present work, a powder nickel-ruthenium based catalyst, unsupported, used in two different schemes of NaBH 4 hydrolysis (alkaline and alkali free hydrolysis), performed in batch reactors with different volumes and bottom geometries (flat and conical), was investigated in terms of durability and reutilization capabilities, throughout 300 cycles. For the alkaline NaBH 4 hydrolysis, the H 2 generation rate progressively decreases with catalyst reused and only ∼25% of the initial H 2 generation rate remains after 300 reutilizations. For similar periods of catalyst aging, it was observed that the reactor conical bottom shape greatly enhances the H 2 generation rate (and practically eliminates the reaction induction time) in the solid or alkali free NaBH 4 hydrolysis, and, as a result, the values obtained for the H 2 generation rates, even after 300 extensive cycling, are above the range of the greatest values reported so far in the open literature. The catalyst, before and after 300 reutilizations, was characterized by textural properties based on nitrogen adsorption isotherms; by surface morphology using scanning electron microscopy (SEM) coupled with EDS spectroscopy and by X-ray photoelectron spectroscopy (XPS). The deterioration of the catalyst seems to be caused by ruthenium segregation from the Ni-Ru alloy, which brought to diminishing the catalyst performance throughout its 300 long-life reutilizations. Nevertheless, the capability of reutilization of the developed nickel-based bimetallic catalyst is a major finding bearing in mind the possible application of this concept for hydrogen generation and storage. The present work gives emphasis to the importance of considering different schemes of NaBH 4 hydrolysis in the study of catalyst durability and calls for increased caution in considering the reactor bottom geometry in those schemes. © 2011 Elsevier B.V.